The Application of Breastfeeding Technique Education on Breastfeeding Effectiveness in Post-Cesarean Section Mothers at Ir. Soekarno Regional Hospital, Sukoharjo - Rahmawati, Andri Magfiroh; Silvitasari, Ika; Prastiwi, Yohana Ika (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Background: Cesarean section is a surgical procedure to deliver a baby by opening the maternal abdominal and uterine walls. One common problem following CS is difficulty in breastfeeding, which can interfere with breast milk stimulation. Proper breastfeeding technique, involving correct positioning of the mother and infant, is essential for successful breastfeeding. Objective: To determine the effect of breastfeeding technique education on breastfeeding effectiveness among post-CS mothers at Ir. Soekarno Regional Hospital, Sukoharjo Regency. Methods: The research design used is a descriptive case study. Results: From the results of the application of breastfeeding technique education for 2 days, it was shown that there was an increase in breastfeeding effectiveness. In Mrs. N, the effectiveness of breastfeeding with a value of 4 (effective enough breastfeeding) increased to a value of 8 (effective breastfeeding was good), while in Mrs. S the effectiveness of breastfeeding with a value of 5 (effectiveness of adequate breastfeeding) increased to a value of 9 (effective breastfeeding was good). Conclusion: There was an increase in breastfeeding effectiveness in mothers after applying breastfeeding education techniques for 2 days.